1995
DOI: 10.1111/j.1467-8624.1995.tb00934.x
|View full text |Cite
|
Sign up to set email alerts
|

Community Level Factors and Child Maltreatment Rates

Abstract: Using census and administrative agency data for 177 urban census tracts, variation in rates of officially reported child maltreatment is found to be related to structural determinants of community social organization: economic and family resources, residential instability, household and age structure, and geographic proximity of neighborhoods to concentrated poverty. Furthermore, child maltreatment rates are found to be intercorrelated with other indicators of the breakdown of community social control and orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
143
1
3

Year Published

1999
1999
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(155 citation statements)
references
References 35 publications
3
143
1
3
Order By: Relevance
“…Based on a review of literature, we identified 20 census variables that have been used consistently to approximate neighborhood-level environments for possible inclusion in the deprivation index. These measures included the following * : one education variable, 47,48 two employment, 49,50 five housing, [51][52][53] four variables representing occupation, 10,54 five poverty, [55][56][57][58] one racial composition, 51,59 and two residential stability.…”
Section: Data Reduction and Exposure Definitionmentioning
confidence: 99%
“…Based on a review of literature, we identified 20 census variables that have been used consistently to approximate neighborhood-level environments for possible inclusion in the deprivation index. These measures included the following * : one education variable, 47,48 two employment, 49,50 five housing, [51][52][53] four variables representing occupation, 10,54 five poverty, [55][56][57][58] one racial composition, 51,59 and two residential stability.…”
Section: Data Reduction and Exposure Definitionmentioning
confidence: 99%
“…9 Several studies have reported associations between economic factors and maltreatment rates at the neighborhood and community levels. [12][13][14][15] Recently, a retrospective study of children admitted to 38 hospitals between 2000 and 2009 showed that rates of admissions for physical abuse and high-risk traumatic brain injury were significantly related to increases in local mortgage foreclosure and delinquency rates in the associated metropolitan areas. 16 Although there is considerable evidence that income inequality has a negative impact on health and wellbeing for both adults and children, and that poverty is associated with rates of child maltreatment, no study has examined the association of income inequality with child maltreatment.…”
mentioning
confidence: 99%
“…For example, substandard or vacant housing, overcrowding, and residential instability are also linked to child abuse risk (as reviewed in Coulton et al, 2007). Child maltreatment rates in neighborhoods also have been shown to correlate with other indicators of social distress, such as infant mortality, juvenile delinquency, violent crime, and drug trafficking (Coulton, Korbin, Su, & Chow, 1995).…”
Section: Environment and Social Network Factorsmentioning
confidence: 99%